Carrying capacity of hiking trails in Natura 2000 sites: a case study from North Atlantic Islands (Azores, Portugal) - Queiroz,Rose Emília (2014)
Tourism has registered a significant growth in the Azores representing already 15.2% of its regional Gross Domestic Product (GDP). Because an increase in the touristic activity may affect the quality of natural habitats, it is very important to evaluate the size of those impacts in order to take sustainable management measures. In this context, hiking trails are one of the most searched activities in the Azores in natural areas, and as such it is important to understand if they are under human pressure. This study aimed to determine the Tourism Carrying Capacity (TCC) of hiking trails crossing Special Areas of Conservations (SAC) of Natura 2000, in two of the nine Azorean islands, São Miguel and Flores; it also aimed to evaluate the potential of TCC as a management tool for development and planning of a sustainable tourism, for those areas. The Real Carrying Capacity (RCC) of the trails was determined by the Cifuentes method, based on the Physical Carrying Capacity (PCC) modified by correction factors (social, precipitation, light and accessibility), selected according to the tourist activity and the conditions of the study area. The correction factor that negatively influenced the RCC the most, for all the trails, was the social factor followed by light. The minor RCC registered (118 visitors/day) was reported to the trail Lagoa do Fogo-Monte Escuro (São Miguel), while the greatest value (557 visitors/day) was calculated for the trail Ponta Delgada-Fajã Grande (Flores). In both trails correction factors social and light, were also the ones that most influenced the RCC. Even considering that the RCC has not yet been achieved in any of the studied trails, and that the Effective Carrying Capacity (ECC) has not been evaluated, it is relevant to keep monitoring those factors, since they are linked to the quality of the visit.